IDH-wildtype lower-grade diffuse gliomas: the importance of histological grade and molecular assessment for prognostic stratification. Issue 6 (11th November 2020) - Berzero, Giulia; Di Stefano, Anna Luisa; Ronchi, Susanna; Bielle, Franck; Villa, Chiara; Guillerm, Erell; Capelle, Laurent; Mathon, Bertrand; Laurenge, Alice; Giry, Marine; Schmitt, Yohann; Marie, Yannick; et al.
Abstract: Background: Isocitrate dehydrogenase ( IDH ) wildtype (wt) grade II gliomas are a rare and heterogeneous entity. Survival and prognostic factors are poorly defined. Methods: We searched retrospectively all patients diagnosed with diffuse World Health Organization (WHO) grades II and III gliomas at our center (1989–2020). Results: Out of 517 grade II gliomas, 47 were "diffuse astrocytomas, IDH wt." Tumors frequently had fronto-temporo-insular location (28/47, 60%) and infiltrative behavior. We found telomerase reverse transcriptase ( TERT ) promoter mutations (23/45, 51%), whole chromosome 7 gains (10/37, 27%), whole chromosome 10 losses (10/41, 24%), and EGFR amplifications (4/43, 9%), but no TP53 mutations (0/22, 0%). Median overall survival (OS) was 59 months (vs 19 mo for IDH wt grade III gliomas) ( P < 0.0001). Twenty-nine patients (29/43, 67%) met the definition of molecular glioblastoma according to cIMPACT-NOW update 3. Median OS in this subset was 42 months, which was shorter compared with patients with IDH wt grade II gliomas not meeting this definition (median OS: 57 mo), but substantially longer compared with IDH wt grade III gliomas meeting the definition for molecular glioblastoma (median OS: 17 mo, P < 0.0001). Most patients with IDH wt grade II gliomas met cIMPACT criteria because of isolated TERT promoter mutations (16/26, 62%), which were not predictive of poor outcome (median OS: 88 mo). Actionable targets, including 5 gene fusions involving FGFR3, were found in 7 patients (24%). Conclusions: Our findings highlight the importance of histological grading and molecular profiling for the prognostic stratification of IDH wt gliomas and suggest some caution when assimilating IDH wt grade II gliomas to molecular glioblastomas, especially those with isolated TERT promoter mutation.